Соціокультурні аспекти впливу гендеру на метафору - Пірська, Христина Олександрівна; Pirska, Kh. O. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті здійснено короткий огляд наукового доробку в західному та російському мовознавстві, який стосується вивчення образних засобів у взаємозв’язку із соціокультурною категорією статі. Описано основні результати попередніх досліджень. Проілюстровано соціальні чинники, що впливають на вибір образних засобів. Наведено аргументи, які підтверджують гіпотезу нашого дослідження. Представлено основні етапи його проведення, принципи вибирання фактичного матеріалу та його класифікації. This article provides a short overview of the scientific researches in Western and Russian linguistics, concerning the study of the tropes in correlation with sociocultural notion of gender. The main results of the previous researches are discussed. Social factors that influence the choice of figurative means are illustrated. The arguments, which confirm the hypothesis of our research, are provided. The main stages of our research are represented as well as the principles of the factual material gathering and its classification. The given overview showed that foreign linguists pay not enough attention to the raised issue, especially when we speak about simultaneous crosscultural and gender analysis of the metaphorisation process in contemporary literary discourse. Moreover, a lot of facts indicate the possibility of such differences in male and female writers’ speech. It is confirmed not only by the results of previous researches but also by the results of our previous statistical analysis.
Sociocultural Influences of Gender on Metaphors
Keywords: гендер; gender; метафора; metaphor; метафорична номінація; metaphorical nomination